CONSTRUCTION OF THE GENERALISED qπ‘žq–DERIVATIVE OPERATORS







Dayanand Parashar
Department of Physics, A.R.S.D. College, University of Delhi
New Delhi - 110021, India


Deepak Parashar
Department of Mathematics, University of Wales Swansea, Singleton Park
Swansea SA2 8PP, United Kingdom
D.Parashar@swansea.ac.uk
http://www-maths.swan.ac.uk/staff/dp/








Abstract

This investigation pertains to the construction of a class of generalised deformed derivative operators which furnish the familiar finite difference and the qπ‘žq–derivatives as special cases. The procedure involves the introduction of a linear operator which is multiplicative over functions of a real variable. The validity of the general prescriptions is ascertained by considering suitable examples of such derivatives and constructing their eigenfunctions explicitly. The relationship of a particular version of the operator with the one-dimensional MΓΆbius transformation is also established.

MSC: 05A30; 26A24; 81R50
Keywords: qπ‘žq–derivatives; qπ‘žq–calculus; MΓΆbius transformations





J. Geom. Phys. 48 (2003) 297–308

1 Introduction

Ever since the pioneering work of Jackson [1], there have been numerous attempts [2, 3, 4] to carry out investigation into various aspects of deformations which have played a crucial role in the understanding of important mathematical and physical concepts. A concrete realisation of such attributes is easily traced to the emergence of quantum groups [5, 6], embodying appropriate deformations of algebraic and geometric structures in a particularly elegant formulation. While there are several ways in which to study deformations, perhaps the most essential ingredients in such a study would invariably comprise, for instance, the qπ‘žq–deformed derivative operators, coordinate multiplication operators, etc., among others. Significantly, these qπ‘žq–deformed operators have met with tremendous success when applied to a host of problems, most notably in the realm of oscillator algebra [2, 7, 8] and qπ‘žq–calculus [9]. This offers the main motivation to seek a generalisation of these operators in order to be able to try applications of the underlying prescriptions to a wider class of systems.

In Sec. 222, we construct a generalised deformed derivative operator and study the corresponding eigenfunctions. Sec. 333 is devoted to a discussion of specific examples of the generalised version of this operator where we explicitly demonstrate the salient features for the purpose of applications. A possible connection of the deformed operator with the reduced MΓΆbius transformation operator is discussed in Sec. 444. Concluding remarks form contents of Sec. 555.

2 The Deformed Derivative

To facilitate construction of the generalised deformed derivative, we consider a linear operator Ξ©^^Ξ©\hat{\Omega}\, whose action on the product of two functions, say f​(x)𝑓π‘₯f(x) and g​(x)𝑔π‘₯g(x), xβˆˆβ„π‘₯ℝx\in\mathbb{R}, can be written as

Ξ©^​{f​(x)​g​(x)}={Ξ©^​f​(x)}​{Ξ©^​g​(x)}=f​(Ξ©^​x)​g​(Ξ©^​x)^Ω𝑓π‘₯𝑔π‘₯^Ω𝑓π‘₯^Ω𝑔π‘₯𝑓^Ξ©π‘₯𝑔^Ξ©π‘₯\hat{\Omega}\,\{f(x)g(x)\}=\{\hat{\Omega}\,f(x)\}\{\hat{\Omega}\,g(x)\}=f(\hat{\Omega}\,x)g(\hat{\Omega}\,x) (2.1)

clearly displaying the property that Ξ©^^Ξ©\hat{\Omega}\, is multiplicative over functions of xπ‘₯x. We further assign to Ξ©^^Ξ©\hat{\Omega}\, dependence on a parameter Ξ»πœ†\lambda such that Ξ©^β†’Iβ†’^Ω𝐼\hat{\Omega}\,\rightarrow I (the identity operator) in the limit Ξ»β†’0β†’πœ†0\lambda\rightarrow 0. This requirement is necessitated by the desire to accomplish meaningful comparisons with the more familiar derivative operators. In particular, the translation operator Ξ©=H^=ehβ€‹βˆ‚xΞ©^𝐻superscriptπ‘’β„Žsubscriptπ‘₯\Omega=\hat{H}\,=e^{h\partial_{x}} such that H^​f​(x)=f​(x+h)^𝐻𝑓π‘₯𝑓π‘₯β„Ž\hat{H}\,f(x)=f(x+h), while the qπ‘žq–dilation operator Ξ©=Q^=eln⁑(q)​xβ€‹βˆ‚xΞ©^𝑄superscriptπ‘’π‘žπ‘₯subscriptπ‘₯\Omega=\hat{Q}\,=e^{\ln(q)x{\partial}_{x}} such that Q^​f​(x)=f​(q​x)^𝑄𝑓π‘₯π‘“π‘žπ‘₯\hat{Q}\,f(x)=f(qx) form examples of such an operator. An appropriate generalisation of the deformed derivative operator is constructed through the definition

DxΞ©={1(Ξ©^βˆ’I)​x}​(Ξ©^βˆ’I)subscriptsubscript𝐷π‘₯Ξ©1^Ω𝐼π‘₯^Ω𝐼~{}_{\Omega}D_{x}=\left\{\frac{1}{(\hat{\Omega}\,-I)x}\right\}\left(\hat{\Omega}\,-I\right) (2.2)

which, operating on any function f​(x)𝑓π‘₯f(x), gives

DxΩ​f​(x)=f​(Ξ©^​x)βˆ’f​(x)(Ξ©^​x)βˆ’xsubscriptsubscript𝐷π‘₯Ω𝑓π‘₯𝑓^Ξ©π‘₯𝑓π‘₯^Ξ©π‘₯π‘₯~{}_{\Omega}D_{x}f(x)=\frac{f(\hat{\Omega}\,x)-f(x)}{(\hat{\Omega}\,x)-x} (2.3)

It follows immediately that DxΩ​x=1subscriptsubscript𝐷π‘₯Ξ©π‘₯1~{}_{\Omega}D_{x}x=1 and DxΩ​c=0subscriptsubscript𝐷π‘₯Ω𝑐0~{}_{\Omega}D_{x}c=0 for any constant c𝑐c.

Proposition 1

The deformed derivative DxΞ©subscriptsubscript𝐷π‘₯Ξ©~{}_{\Omega}D_{x} obeys two modified Leibniz rules

DxΩ​{f​(x)​g​(x)}={DxΩ​f​(x)}​g​(x)+{Ξ©^​f​(x)}​DxΩ​g​(x)subscriptsubscript𝐷π‘₯Ω𝑓π‘₯𝑔π‘₯subscriptsubscript𝐷π‘₯Ω𝑓π‘₯𝑔π‘₯^Ω𝑓π‘₯subscriptsubscript𝐷π‘₯Ω𝑔π‘₯~{}_{\Omega}D_{x}\{f(x)g(x)\}=\{~{}_{\Omega}D_{x}f(x)\}g(x)+\{\hat{\Omega}\,f(x)\}~{}_{\Omega}D_{x}g(x) (2.4)
DxΩ​{f​(x)​g​(x)}=f​(x)​{DxΩ​g​(x)}+{DxΩ​f​(x)}​Ω^​g​(x)subscriptsubscript𝐷π‘₯Ω𝑓π‘₯𝑔π‘₯𝑓π‘₯subscriptsubscript𝐷π‘₯Ω𝑔π‘₯subscriptsubscript𝐷π‘₯Ω𝑓π‘₯^Ω𝑔π‘₯~{}_{\Omega}D_{x}\{f(x)g(x)\}=f(x)\{~{}_{\Omega}D_{x}g(x)\}+\{~{}_{\Omega}D_{x}f(x)\}\hat{\Omega}\,g(x) (2.5)

and the chain rule

DxΩ​f​(g​(x))=Dg​(x)Ω​f​(g​(x))​DxΩ​g​(x)subscriptsubscript𝐷π‘₯Ω𝑓𝑔π‘₯subscriptsubscript𝐷𝑔π‘₯Ω𝑓𝑔π‘₯subscriptsubscript𝐷π‘₯Ω𝑔π‘₯~{}_{\Omega}D_{x}f(g(x))={~{}_{\Omega}D}_{g(x)}f(g(x))~{}_{\Omega}D_{x}g(x) (2.6)

Proof:

DxΩ​{f​(x)​g​(x)}subscriptsubscript𝐷π‘₯Ω𝑓π‘₯𝑔π‘₯\displaystyle~{}_{\Omega}D_{x}\{f(x)g(x)\} =\displaystyle= 1(Ξ©^βˆ’I)​x​{Ξ©^​f​(x)​g​(x)βˆ’f​(x)​g​(x)}1^Ω𝐼π‘₯^Ω𝑓π‘₯𝑔π‘₯𝑓π‘₯𝑔π‘₯\displaystyle\frac{1}{(\hat{\Omega}\,-I)x}\left\{\hat{\Omega}\,f(x)g(x)-f(x)g(x)\right\}
=\displaystyle= 1(Ξ©^βˆ’I)​x{[f(Ξ©^x)]g(x)βˆ’[f(Ξ©^x)]g(x)\displaystyle\frac{1}{(\hat{\Omega}\,-I)x}\{[f(\hat{\Omega}\,x)]g(x)-[f(\hat{\Omega}\,x)]g(x)
+f(Ξ©^x)g(Ξ©^x)βˆ’f(x)g(x)}\displaystyle\hfill+f(\hat{\Omega}\,x)g(\hat{\Omega}\,x)-f(x)g(x)\}
=\displaystyle= 1(Ξ©^βˆ’I)​x​{[f​(Ξ©^​x)βˆ’f​(x)]​g​(x)+f​(Ξ©^​x)​[g​(Ξ©^​x)βˆ’g​(x)]}1^Ω𝐼π‘₯delimited-[]𝑓^Ξ©π‘₯𝑓π‘₯𝑔π‘₯𝑓^Ξ©π‘₯delimited-[]𝑔^Ξ©π‘₯𝑔π‘₯\displaystyle\frac{1}{(\hat{\Omega}\,-I)x}\left\{[f(\hat{\Omega}\,x)-f(x)]g(x)+f(\hat{\Omega}\,x)[g(\hat{\Omega}\,x)-g(x)]\right\}
=\displaystyle= {f​(Ξ©^​x)βˆ’f​(x)(Ξ©^​x)βˆ’x}​g​(x)+f​(Ξ©^​x)​{g​(Ξ©^​x)βˆ’g​(x)(Ξ©^​x)βˆ’x}𝑓^Ξ©π‘₯𝑓π‘₯^Ξ©π‘₯π‘₯𝑔π‘₯𝑓^Ξ©π‘₯𝑔^Ξ©π‘₯𝑔π‘₯^Ξ©π‘₯π‘₯\displaystyle\left\{\frac{f(\hat{\Omega}\,x)-f(x)}{(\hat{\Omega}\,x)-x}\right\}g(x)+f(\hat{\Omega}\,x)\left\{\frac{g(\hat{\Omega}\,x)-g(x)}{(\hat{\Omega}\,x)-x}\right\}
=\displaystyle= {DxΩ​f​(x)}​g​(x)+Ξ©^​f​(x)​{DxΩ​g​(x)}subscriptsubscript𝐷π‘₯Ω𝑓π‘₯𝑔π‘₯^Ω𝑓π‘₯subscriptsubscript𝐷π‘₯Ω𝑔π‘₯\displaystyle\left\{~{}_{\Omega}D_{x}f(x)\right\}g(x)+\hat{\Omega}\,f(x)\left\{~{}_{\Omega}D_{x}g(x)\right\}

The second Leibniz rule (2.5) follows from the first if we simply interchange the roles of f𝑓f and g𝑔g. To prove the modified chain rule, we have

DxΩ​{f∘g}​(x)subscriptsubscript𝐷π‘₯Ω𝑓𝑔π‘₯\displaystyle~{}_{\Omega}D_{x}\{f\circ g\}(x) =\displaystyle= {f∘g}​(Ξ©^​x)βˆ’{f∘g}​(x)(Ξ©^​x)βˆ’x𝑓𝑔^Ξ©π‘₯𝑓𝑔π‘₯^Ξ©π‘₯π‘₯\displaystyle\frac{\{f\circ g\}(\hat{\Omega}\,x)-\{f\circ g\}(x)}{(\hat{\Omega}\,x)-x}
=\displaystyle= {f​(g​(Ξ©^​x))βˆ’f​(g​(x))g​(Ξ©^​x)βˆ’g​(x)}​{g​(Ξ©^​x)βˆ’g​(x)(Ξ©^​x)βˆ’x}𝑓𝑔^Ξ©π‘₯𝑓𝑔π‘₯𝑔^Ξ©π‘₯𝑔π‘₯𝑔^Ξ©π‘₯𝑔π‘₯^Ξ©π‘₯π‘₯\displaystyle\left\{\frac{f(g(\hat{\Omega}\,x))-f(g(x))}{g(\hat{\Omega}\,x)-g(x)}\right\}\left\{\frac{g(\hat{\Omega}\,x)-g(x)}{(\hat{\Omega}\,x)-x}\right\}
=\displaystyle= {(Ξ©^βˆ’I)​f​(g​(x))(Ξ©^βˆ’I)​g​(x)}​{(Ξ©^βˆ’I)​g​(x)(Ξ©^βˆ’I)​x}^Ω𝐼𝑓𝑔π‘₯^Ω𝐼𝑔π‘₯^Ω𝐼𝑔π‘₯^Ω𝐼π‘₯\displaystyle\left\{\frac{(\hat{\Omega}\,-I)f(g(x))}{(\hat{\Omega}\,-I)g(x)}\right\}\left\{\frac{(\hat{\Omega}\,-I)g(x)}{(\hat{\Omega}\,-I)x}\right\}
=\displaystyle= Dg​(x)Ω​f​(g​(x))​DxΩ​g​(x)subscriptsubscript𝐷𝑔π‘₯Ω𝑓𝑔π‘₯subscriptsubscript𝐷π‘₯Ω𝑔π‘₯\displaystyle{~{}_{\Omega}D}_{g(x)}f(g(x))~{}_{\Omega}D_{x}g(x)

In the limit Ξ»β†’0β†’πœ†0\lambda\rightarrow 0, we see that DxΞ©β†’dd​x=βˆ‚xβ†’subscriptsubscript𝐷π‘₯Ω𝑑𝑑π‘₯subscriptπ‘₯~{}_{\Omega}D_{x}\rightarrow\frac{d}{dx}={\partial}_{x}. Note that this generalised derivative specialises to the familiar finite difference derivative Ξ”xhsubscriptsubscriptΞ”π‘₯β„Ž~{}_{h}\Delta_{x}:

Ξ”xh​f​(x)=f​(x+h)βˆ’f​(x)hsubscriptsubscriptΞ”π‘₯β„Žπ‘“π‘₯𝑓π‘₯β„Žπ‘“π‘₯β„Ž~{}_{h}\Delta_{x}f(x)=\frac{f(x+h)-f(x)}{h}

and the qπ‘žq–derivative Dxqsubscriptsubscript𝐷π‘₯π‘ž~{}_{q}D_{x}:

Dxq​f​(x)=f​(q​x)βˆ’f​(x)(qβˆ’1)​xsubscriptsubscript𝐷π‘₯π‘žπ‘“π‘₯π‘“π‘žπ‘₯𝑓π‘₯π‘ž1π‘₯~{}_{q}D_{x}f(x)=\frac{f(qx)-f(x)}{(q-1)x}

as expected.

2.1 Inverse deformed derivative (Dxβˆ’1Ξ©subscriptsubscriptsuperscript𝐷1π‘₯Ξ©~{}_{\Omega}D^{-1}_{x})

The nonsingular behaviour of the operator DxΞ©subscriptsubscript𝐷π‘₯Ξ©~{}_{\Omega}D_{x} can be ascertained only if the existence of its inverse Dxβˆ’1Ξ©subscriptsubscriptsuperscript𝐷1π‘₯Ξ©~{}_{\Omega}D^{-1}_{x} is guaranteed. Consequently, the condition DxΩ∘Dxβˆ’1Ξ©=Isubscriptsubscript𝐷π‘₯Ξ©subscriptsubscriptsuperscript𝐷1π‘₯Ω𝐼~{}_{\Omega}D_{x}\circ~{}_{\Omega}D^{-1}_{x}=I must necessarily be satisfied on analytic functions. We, therefore, proceed to define such an inverse. The operation of the deformed derivative DxΞ©subscriptsubscript𝐷π‘₯Ξ©~{}_{\Omega}D_{x} on an arbitrary analytic function f​(x)𝑓π‘₯f(x) can be rewritten in the form

DxΩ​f​(x)=1(Iβˆ’Ξ©^)​x​(Iβˆ’Ξ©^)​f​(x)subscriptsubscript𝐷π‘₯Ω𝑓π‘₯1𝐼^Ξ©π‘₯𝐼^Ω𝑓π‘₯~{}_{\Omega}D_{x}f(x)=\frac{1}{(I-\hat{\Omega}\,)x}\left(I-\hat{\Omega}\,\right)f(x) (2.7)

which allows us to formally invert the operator DxΞ©subscriptsubscript𝐷π‘₯Ξ©~{}_{\Omega}D_{x} to get the inverse operator Dxβˆ’1Ξ©subscriptsubscriptsuperscript𝐷1π‘₯Ξ©~{}_{\Omega}D^{-1}_{x} through the definition

Dxβˆ’1Ξ©=βˆ‘j=0∞Ω^j​{(Iβˆ’Ξ©^)​x}subscriptsubscriptsuperscript𝐷1π‘₯Ξ©superscriptsubscript𝑗0superscript^Ω𝑗𝐼^Ξ©π‘₯~{}_{\Omega}D^{-1}_{x}=\sum_{j=0}^{\infty}{\hat{\Omega}\,}^{j}\left\{(I-\hat{\Omega}\,)x\right\} (2.8)

As an illustrative example, let us compute the operation of Dxβˆ’1Ξ©subscriptsubscriptsuperscript𝐷1π‘₯Ξ©~{}_{\Omega}D^{-1}_{x} on f​(x)=xn𝑓π‘₯superscriptπ‘₯𝑛f(x)=x^{n} (say). We then have

Dxβˆ’1Ω​xnsubscriptsubscriptsuperscript𝐷1π‘₯Ξ©superscriptπ‘₯𝑛\displaystyle~{}_{\Omega}D^{-1}_{x}\ x^{n} =\displaystyle= βˆ‘j=0∞Ω^j​{(Iβˆ’Ξ©^)​x}​xnsuperscriptsubscript𝑗0superscript^Ω𝑗𝐼^Ξ©π‘₯superscriptπ‘₯𝑛\displaystyle\sum_{j=0}^{\infty}{\hat{\Omega}\,}^{j}\left\{(I-\hat{\Omega}\,)x\right\}x^{n} (2.9)
=\displaystyle= βˆ‘j=0∞Ω^j​{xn+1βˆ’(Ξ©^​x)​xn}superscriptsubscript𝑗0superscript^Ω𝑗superscriptπ‘₯𝑛1^Ξ©π‘₯superscriptπ‘₯𝑛\displaystyle\sum_{j=0}^{\infty}{\hat{\Omega}\,}^{j}\left\{x^{n+1}-(\hat{\Omega}\,x)x^{n}\right\}
=\displaystyle= βˆ‘j=0∞{Ξ©^j​xn+1βˆ’(Ξ©^j+1​x)​(Ξ©^j​xn)}superscriptsubscript𝑗0superscript^Ω𝑗superscriptπ‘₯𝑛1superscript^Ω𝑗1π‘₯superscript^Ω𝑗superscriptπ‘₯𝑛\displaystyle\sum_{j=0}^{\infty}\left\{{\hat{\Omega}\,}^{j}x^{n+1}-({\hat{\Omega}\,}^{j+1}x)({\hat{\Omega}\,}^{j}x^{n})\right\}

The operation of DxΞ©subscriptsubscript𝐷π‘₯Ξ©~{}_{\Omega}D_{x} on (2.9) gives

DxΩ∘Dxβˆ’1Ω​xnsubscriptsubscript𝐷π‘₯Ξ©subscriptsubscriptsuperscript𝐷1π‘₯Ξ©superscriptπ‘₯𝑛\displaystyle~{}_{\Omega}D_{x}\circ~{}_{\Omega}D^{-1}_{x}x^{n} =\displaystyle= DxΞ©β€‹βˆ‘j=0∞{Ξ©^j​xn+1βˆ’(Ξ©^j+1​x)​(Ξ©^j​xn)}subscriptsubscript𝐷π‘₯Ξ©superscriptsubscript𝑗0superscript^Ω𝑗superscriptπ‘₯𝑛1superscript^Ω𝑗1π‘₯superscript^Ω𝑗superscriptπ‘₯𝑛\displaystyle~{}_{\Omega}D_{x}\sum_{j=0}^{\infty}\left\{{\hat{\Omega}\,}^{j}x^{n+1}-({\hat{\Omega}\,}^{j+1}x)({\hat{\Omega}\,}^{j}x^{n})\right\}
=\displaystyle= (1(Ξ©^​x)βˆ’x){Ξ©^βˆ‘j=0∞{Ξ©^jxn+1βˆ’(Ξ©^j+1x)(Ξ©^jxn)}\displaystyle\left(\frac{1}{(\hat{\Omega}\,x)-x}\right)\Bigg{\{}\hat{\Omega}\,\sum_{j=0}^{\infty}\left\{{\hat{\Omega}\,}^{j}x^{n+1}-({\hat{\Omega}\,}^{j+1}x)({\hat{\Omega}\,}^{j}x^{n})\right\}
Β βˆ’βˆ‘j=0∞{Ξ©^jxn+1βˆ’(Ξ©^j+1x)(Ξ©^jxn)}}\displaystyle\mbox{\hskip 71.13188pt}-\sum_{j=0}^{\infty}\left\{{\hat{\Omega}\,}^{j}x^{n+1}-({\hat{\Omega}\,}^{j+1}x)({\hat{\Omega}\,}^{j}x^{n})\right\}\Bigg{\}}
=\displaystyle= (1(Ξ©^​x)βˆ’x){βˆ‘j=0∞{Ξ©^j+1xn+1βˆ’(Ξ©^j+2x)(Ξ©^j+1xn)\displaystyle\left(\frac{1}{(\hat{\Omega}\,x)-x}\right)\Bigg{\{}\sum_{j=0}^{\infty}\big{\{}{\hat{\Omega}\,}^{j+1}x^{n+1}-({\hat{\Omega}\,}^{j+2}x)({\hat{\Omega}\,}^{j+1}x^{n})
Β βˆ’Ξ©^jxn+1+(Ξ©^j+1x)(Ξ©^jxn)}}\displaystyle\mbox{\hskip 71.13188pt}-{\hat{\Omega}\,}^{j}x^{n+1}+({\hat{\Omega}\,}^{j+1}x)({\hat{\Omega}\,}^{j}x^{n})\big{\}}\Bigg{\}}
=\displaystyle= (1(Ξ©^​x)βˆ’x){Ξ©^xn+1βˆ’(Ξ©^2x)(Ξ©^xn)βˆ’xn+1+(Ξ©^x)xn+\displaystyle\left(\frac{1}{(\hat{\Omega}\,x)-x}\right)\Bigg{\{}\hat{\Omega}\,x^{n+1}-({\hat{\Omega}\,}^{2}x)(\hat{\Omega}\,x^{n})-x^{n+1}+(\hat{\Omega}\,x)x^{n}+
Β Ξ©^2xn+1βˆ’(Ξ©^3x)(Ξ©^2xn)βˆ’(Ξ©^xn+1)+(Ξ©^2x)(Ξ©^xn)+β‹―}\displaystyle\mbox{\hskip 71.13188pt}\hat{\Omega}\,^{2}x^{n+1}-(\hat{\Omega}\,^{3}x)(\hat{\Omega}\,^{2}x^{n})-(\hat{\Omega}\,x^{n+1})+(\hat{\Omega}\,^{2}x)(\hat{\Omega}\,x^{n})+\cdots\Bigg{\}}
=\displaystyle= (1(Ξ©^​x)βˆ’x)​{(Ξ©^​x)​xnβˆ’xn+1}1^Ξ©π‘₯π‘₯^Ξ©π‘₯superscriptπ‘₯𝑛superscriptπ‘₯𝑛1\displaystyle\left(\frac{1}{(\hat{\Omega}\,x)-x}\right)\left\{(\hat{\Omega}\,x)x^{n}-x^{n+1}\right\}
=\displaystyle= xnsuperscriptπ‘₯𝑛\displaystyle x^{n}

Hence the necessary condition

DxΩ∘Dxβˆ’1Ξ©=Isubscriptsubscript𝐷π‘₯Ξ©subscriptsubscriptsuperscript𝐷1π‘₯Ω𝐼~{}_{\Omega}D_{x}\circ\!~{}_{\Omega}D^{-1}_{x}=I (2.10)

is satisfied by the inverse derivative Dxβˆ’1Ξ©subscriptsubscriptsuperscript𝐷1π‘₯Ξ©~{}_{\Omega}D^{-1}_{x}.

2.2 Eigenfunctions

The eigenfunctions of the deformed derivative operator DxΞ©subscriptsubscript𝐷π‘₯Ξ©~{}_{\Omega}D_{x} can be shown to admit a product representation. The following proposition justifies this statement.

Proposition 2

If

DxΩ​EΩ​(x)=EΩ​(x)subscriptsubscript𝐷π‘₯Ξ©subscript𝐸Ωπ‘₯subscript𝐸Ωπ‘₯~{}_{\Omega}D_{x}E_{\Omega}(x)=E_{\Omega}(x) (2.11)

then the function EΩ​(x)subscript𝐸Ωπ‘₯E_{\Omega}(x) is given by

EΩ​(x)=∏j=0∞11+Ξ©^j​(Ξ©^βˆ’I)​xsubscript𝐸Ωπ‘₯superscriptsubscriptproduct𝑗011superscript^Ω𝑗^Ω𝐼π‘₯E_{\Omega}(x)=\prod_{j=0}^{\infty}\frac{1}{1+{\hat{\Omega}\,}^{j}(\hat{\Omega}\,-I)x} (2.12)

Proof: Let the function EΩ​(x)subscript𝐸Ωπ‘₯E_{\Omega}(x) be defined as

EΩ​(x)=∏j=0∞cj​(x)subscript𝐸Ωπ‘₯superscriptsubscriptproduct𝑗0subscript𝑐𝑗π‘₯E_{\Omega}(x)=\prod_{j=0}^{\infty}c_{j}(x) (2.13)

where cj​(x)subscript𝑐𝑗π‘₯c_{j}(x) is a sequence of functions of xπ‘₯x

cj​(x)=Ξ©^j​c0​(x)=c0​(Ξ©^j​x)subscript𝑐𝑗π‘₯superscript^Ω𝑗subscript𝑐0π‘₯subscript𝑐0superscript^Ω𝑗π‘₯c_{j}(x)={\hat{\Omega}\,}^{j}c_{0}(x)=c_{0}({\hat{\Omega}\,}^{j}x) (2.14)

Then

DxΩ​EΩ​(x)subscriptsubscript𝐷π‘₯Ξ©subscript𝐸Ωπ‘₯\displaystyle~{}_{\Omega}D_{x}E_{\Omega}(x) =\displaystyle= {1(Ξ©^βˆ’I)​x}​(Ξ©^βˆ’I)β€‹βˆj=0∞cj​(x)1^Ω𝐼π‘₯^Ω𝐼superscriptsubscriptproduct𝑗0subscript𝑐𝑗π‘₯\displaystyle\left\{\frac{1}{(\hat{\Omega}\,-I)x}\right\}\left(\hat{\Omega}\,-I\right)\prod_{j=0}^{\infty}c_{j}(x)
=\displaystyle= {1(Ξ©^βˆ’I)​x}​{∏j=0∞Ω^​cj​(x)βˆ’βˆj=0∞cj​(x)}1^Ω𝐼π‘₯superscriptsubscriptproduct𝑗0^Ξ©subscript𝑐𝑗π‘₯superscriptsubscriptproduct𝑗0subscript𝑐𝑗π‘₯\displaystyle\left\{\frac{1}{(\hat{\Omega}\,-I)x}\right\}\left\{\prod_{j=0}^{\infty}\hat{\Omega}\,c_{j}(x)-\prod_{j=0}^{\infty}c_{j}(x)\right\}
=\displaystyle= {1(Ξ©^βˆ’I)​x}​{∏j=0∞cj+1​(x)βˆ’βˆj=0∞cj​(x)}1^Ω𝐼π‘₯superscriptsubscriptproduct𝑗0subscript𝑐𝑗1π‘₯superscriptsubscriptproduct𝑗0subscript𝑐𝑗π‘₯\displaystyle\left\{\frac{1}{(\hat{\Omega}\,-I)x}\right\}\left\{\prod_{j=0}^{\infty}c_{j+1}(x)-\prod_{j=0}^{\infty}c_{j}(x)\right\}
=\displaystyle= {1(Ξ©^βˆ’I)​x}​{∏j=0∞cj​(x)c0​(x)βˆ’βˆj=0∞cj​(x)}1^Ω𝐼π‘₯superscriptsubscriptproduct𝑗0subscript𝑐𝑗π‘₯subscript𝑐0π‘₯superscriptsubscriptproduct𝑗0subscript𝑐𝑗π‘₯\displaystyle\left\{\frac{1}{(\hat{\Omega}\,-I)x}\right\}\left\{\prod_{j=0}^{\infty}\frac{c_{j}(x)}{c_{0}(x)}-\prod_{j=0}^{\infty}c_{j}(x)\right\}
=\displaystyle= {1(Ξ©^βˆ’I)​x}​{c0βˆ’1​(x)βˆ’1}β€‹βˆj=0∞cj​(x)1^Ω𝐼π‘₯superscriptsubscript𝑐01π‘₯1superscriptsubscriptproduct𝑗0subscript𝑐𝑗π‘₯\displaystyle\left\{\frac{1}{(\hat{\Omega}\,-I)x}\right\}\left\{c_{0}^{-1}(x)-1\right\}\prod_{j=0}^{\infty}c_{j}(x)
=\displaystyle= {1(Ξ©^βˆ’I)​x}​{c0βˆ’1​(x)βˆ’1}​EΩ​(x)1^Ω𝐼π‘₯superscriptsubscript𝑐01π‘₯1subscript𝐸Ωπ‘₯\displaystyle\left\{\frac{1}{(\hat{\Omega}\,-I)x}\right\}\left\{c_{0}^{-1}(x)-1\right\}E_{\Omega}(x)

Since the function c0​(x)subscript𝑐0π‘₯c_{0}(x) (cf. (2.14))is an arbitrary function of xπ‘₯x, we may choose

c0βˆ’1​(x)=1+(Ξ©^​x)βˆ’xsuperscriptsubscript𝑐01π‘₯1^Ξ©π‘₯π‘₯c_{0}^{-1}(x)=1+(\hat{\Omega}\,x)-x (2.15)

so that the functions cj​(x)subscript𝑐𝑗π‘₯c_{j}(x) can be cast in the form

cj​(x)subscript𝑐𝑗π‘₯\displaystyle c_{j}(x) =\displaystyle= Ξ©^j​c0​(x)superscript^Ω𝑗subscript𝑐0π‘₯\displaystyle{\hat{\Omega}\,}^{j}c_{0}(x)
=\displaystyle= c0​(Ξ©^j​x)subscript𝑐0superscript^Ω𝑗π‘₯\displaystyle c_{0}({\hat{\Omega}\,}^{j}x)
=\displaystyle= 11+Ξ©^j​(Ξ©^βˆ’I)​x11superscript^Ω𝑗^Ω𝐼π‘₯\displaystyle\frac{1}{1+{\hat{\Omega}\,}^{j}(\hat{\Omega}\,-I)x}

which, in turn, gives the desired eigenfunction

EΩ​(x)=∏j=0∞11+Ξ©^j​(Ξ©^βˆ’I)​xsubscript𝐸Ωπ‘₯superscriptsubscriptproduct𝑗011superscript^Ω𝑗^Ω𝐼π‘₯E_{\Omega}(x)=\prod_{j=0}^{\infty}\frac{1}{1+{\hat{\Omega}\,}^{j}(\hat{\Omega}\,-I)x} (2.16)

In view of the relation DxΩ​EΩ​(x)=EΩ​(x)subscriptsubscript𝐷π‘₯Ξ©subscript𝐸Ωπ‘₯subscript𝐸Ωπ‘₯~{}_{\Omega}D_{x}E_{\Omega}(x)=E_{\Omega}(x), the eigenfunction EΩ​(x)subscript𝐸Ωπ‘₯E_{\Omega}(x) can be interpreted as the ΩΩ\Omega–exponential function. An alternative description of the eigenfunctions EΩ​(x)subscript𝐸Ωπ‘₯E_{\Omega}(x) proceeds via the series representation in terms of the inverse operator Dxβˆ’1Ξ©subscriptsubscriptsuperscript𝐷1π‘₯Ξ©~{}_{\Omega}D^{-1}_{x}. For this purpose, we write

EΩ​(x)=βˆ‘j=0∞ej​(x)subscript𝐸Ωπ‘₯superscriptsubscript𝑗0subscript𝑒𝑗π‘₯E_{\Omega}(x)=\sum_{j=0}^{\infty}e_{j}(x) (2.17)

where functions ej​(x)subscript𝑒𝑗π‘₯e_{j}(x) are defined as

ej​(x)=DxΩ​ej+1​(x)orDxβˆ’1Ω​ej​(x)=ej+1​(x)formulae-sequencesubscript𝑒𝑗π‘₯subscriptsubscript𝐷π‘₯Ξ©subscript𝑒𝑗1π‘₯orsubscriptsubscriptsuperscript𝐷1π‘₯Ξ©subscript𝑒𝑗π‘₯subscript𝑒𝑗1π‘₯e_{j}(x)=~{}_{\Omega}D_{x}e_{j+1}(x)\qquad\text{or}\qquad~{}_{\Omega}D^{-1}_{x}e_{j}(x)=e_{j+1}(x) (2.18)

with the normalisation e0​(x)=1subscript𝑒0π‘₯1e_{0}(x)=1. Relation (2.17) now becomes

EΩ​(x)=βˆ‘j=0∞(Dxβˆ’1Ξ©)j​e0​(x)=βˆ‘j=0∞(Dxβˆ’1Ξ©)jsubscript𝐸Ωπ‘₯superscriptsubscript𝑗0superscriptsubscriptsubscriptsuperscript𝐷1π‘₯Ω𝑗subscript𝑒0π‘₯superscriptsubscript𝑗0superscriptsubscriptsubscriptsuperscript𝐷1π‘₯Ω𝑗E_{\Omega}(x)=\sum_{j=0}^{\infty}({~{}_{\Omega}D^{-1}_{x}})^{j}e_{0}(x)=\sum_{j=0}^{\infty}({~{}_{\Omega}D^{-1}_{x}})^{j} (2.19)

3 Examples of the Operator Ξ©^Ξ»,ksubscript^Ξ©πœ†π‘˜\hat{\Omega}_{{\lambda},k}\,

As remarked in Sec. 222, the linear operator Ξ©^^Ξ©\hat{\Omega}\, is not only multiplicative over functions of xπ‘₯x, but is also characterised by a deformation parameter Ξ»πœ†\lambda. For a complete specification, however, it carries an additional index kβˆˆβ„€+π‘˜superscriptβ„€k\in\mathbb{Z}^{+} signifying the degree of the operator Ξ©^^Ξ©\hat{\Omega}\,. We illustrate this by considering a class of operators given by

Ξ©^Ξ»,k=exp⁑(βˆ’Ξ»β€‹xk+1β€‹βˆ‚x)subscript^Ξ©πœ†π‘˜πœ†superscriptπ‘₯π‘˜1subscriptπ‘₯\hat{\Omega}_{{\lambda},k}\,=\exp\left({-\lambda x^{k+1}{\partial}_{x}}\right) (3.1)

and study their action on functions of the real variable xπ‘₯x.

Proposition 3

If f​(x)=xn𝑓π‘₯superscriptπ‘₯𝑛f(x)=x^{n}, (nβˆˆβ„€+)𝑛superscriptβ„€(n\in\mathbb{Z}^{+}), then

Ξ©^Ξ»,k​xn={x(1+λ​k​xk)1k}nsubscript^Ξ©πœ†π‘˜superscriptπ‘₯𝑛superscriptπ‘₯superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜π‘›\hat{\Omega}_{{\lambda},k}\,x^{n}=\left\{\frac{x}{\left(1+\lambda kx^{k}\right)^{\frac{1}{k}}}\right\}^{n} (3.2)

Proof: Let us consider the operation

exp⁑(βˆ’Ξ»β€‹xk+1β€‹βˆ‚x)​xnπœ†superscriptπ‘₯π‘˜1subscriptπ‘₯superscriptπ‘₯𝑛\displaystyle\exp\left({-\lambda x^{k+1}{\partial}_{x}}\right)x^{n} =\displaystyle= βˆ‘n=0∞(βˆ’Ξ»)nn!​(xk+1β€‹βˆ‚x)n⁑xnsuperscriptsubscript𝑛0superscriptπœ†π‘›π‘›superscriptsuperscriptπ‘₯π‘˜1subscriptπ‘₯𝑛superscriptπ‘₯𝑛\displaystyle\sum_{n=0}^{\infty}\frac{(-\lambda)^{n}}{n!}\left(x^{k+1}{\partial}_{x}\right)^{n}x^{n} (3.3)
=\displaystyle= xn+(βˆ’Ξ»)​n​xk+n+(βˆ’Ξ»)22!​n​(n+k)​x2​k+n+β‹―superscriptπ‘₯π‘›πœ†π‘›superscriptπ‘₯π‘˜π‘›superscriptπœ†22π‘›π‘›π‘˜superscriptπ‘₯2π‘˜π‘›β‹―\displaystyle x^{n}+(-\lambda)nx^{k+n}+\frac{{(-\lambda)}^{2}}{2!}n(n+k)x^{2k+n}+\cdots
=\displaystyle= xn​{1+(βˆ’nk)​(λ​k​xk)+12!​(βˆ’nk)​(βˆ’nkβˆ’1)​(λ​k​xk)2+β‹―}superscriptπ‘₯𝑛1π‘›π‘˜πœ†π‘˜superscriptπ‘₯π‘˜12π‘›π‘˜π‘›π‘˜1superscriptπœ†π‘˜superscriptπ‘₯π‘˜2β‹―\displaystyle x^{n}\left\{1+\left(\frac{-n}{k}\right)(\lambda kx^{k})+\frac{1}{2!}\left(\frac{-n}{k}\right)\left(\frac{-n}{k}-1\right)(\lambda kx^{k})^{2}+\cdots\right\}
=\displaystyle= xn​(1+λ​k​xk)βˆ’nksuperscriptπ‘₯𝑛superscript1πœ†π‘˜superscriptπ‘₯π‘˜π‘›π‘˜\displaystyle x^{n}\left(1+\lambda kx^{k}\right)^{-\frac{n}{k}}
=\displaystyle= {x(1+λ​k​xk)1k}nsuperscriptπ‘₯superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜π‘›\displaystyle\left\{\frac{x}{\left(1+\lambda kx^{k}\right)^{\frac{1}{k}}}\right\}^{n}

On the other hand, if we consider another class of operators

Ξ©^Ξ»,k=exp⁑(βˆ’Ξ»2​{x^k+1,βˆ‚x})subscript^Ξ©πœ†π‘˜πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯\hat{\Omega}_{{\lambda},k}\,=\exp\left({-\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}}\}\right) (3.4)

where {,}\{\ ,\ \} is the anticommutator, then their operation given by the adjoint action on the position operator x^^π‘₯\hat{x}\, results in the equivalence of (3.1) and (3.4) which can be readily seen as follows:

Ξ©^Ξ»,k​x^​Ω^Ξ»,kβˆ’1subscript^Ξ©πœ†π‘˜^π‘₯subscriptsuperscript^Ξ©1πœ†π‘˜\displaystyle\hat{\Omega}_{{\lambda},k}\,\hat{x}\,\hat{\Omega}^{-1}_{{\lambda},k}\, =\displaystyle= exp⁑(βˆ’Ξ»2​{x^k+1,βˆ‚x})​x^​exp⁑(Ξ»2​{x^k+1,βˆ‚x})πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯^π‘₯πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯\displaystyle\exp\left(-\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}\}\right)\hat{x}\,\exp\left(\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}\}\right) (3.6)
=\displaystyle= x^+[βˆ’Ξ»2​{x^k+1,βˆ‚x},x^]^π‘₯πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯^π‘₯\displaystyle\hat{x}\,+\left[-\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}\},\hat{x}\,\right]
Β +12!​[βˆ’Ξ»2​{x^k+1,βˆ‚x},[βˆ’Ξ»2​{x^k+1,βˆ‚x},x^]]+β‹―Β 12πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯^π‘₯β‹―\displaystyle\mbox{\hskip 14.22636pt}+\frac{1}{2!}\left[-\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}\},\left[-\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}\},\hat{x}\,\right]\right]+\cdots

using the Baker-Campbell-Hausdorff formula. The evaluation of the nested commutators proceeds through the following steps

[βˆ’Ξ»2​{x^k+1,βˆ‚x},x^]πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯^π‘₯\displaystyle\left[-\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}\},\hat{x}\,\right] =\displaystyle= βˆ’Ξ»2​[x^k+1β€‹βˆ‚x+βˆ‚xx^k+1,x^]πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯subscriptπ‘₯superscript^π‘₯π‘˜1^π‘₯\displaystyle-\frac{\lambda}{2}\left[\hat{x}\,^{k+1}{\partial}_{x}+{\partial}_{x}\hat{x}\,^{k+1},\hat{x}\,\right]
=\displaystyle= βˆ’Ξ»β€‹x^k+1πœ†superscript^π‘₯π‘˜1\displaystyle-\lambda\hat{x}\,^{k+1}
=\displaystyle= x^​(βˆ’1k)​(λ​k​x^k)^π‘₯1π‘˜πœ†π‘˜superscript^π‘₯π‘˜\displaystyle\hat{x}\,\left(-\frac{1}{k}\right)\left(\lambda k\hat{x}\,^{k}\right)
[βˆ’Ξ»2​{x^k+1,βˆ‚x},[βˆ’Ξ»2​{x^k+1,βˆ‚x},x^]]πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯^π‘₯\displaystyle\left[-\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}\},\left[-\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}\},\hat{x}\,\right]\right] =\displaystyle= [βˆ’Ξ»2​{x^k+1,βˆ‚x},βˆ’Ξ»β€‹x^k+1]πœ†2superscript^π‘₯π‘˜1subscriptπ‘₯πœ†superscript^π‘₯π‘˜1\displaystyle\left[-\frac{\lambda}{2}\{\hat{x}\,^{k+1},{\partial}_{x}\},-\lambda\hat{x}\,^{k+1}\right]
=\displaystyle= Ξ»2​(k+1)​x^2​k+1superscriptπœ†2π‘˜1superscript^π‘₯2π‘˜1\displaystyle{\lambda}^{2}(k+1)\hat{x}\,^{2k+1}
=\displaystyle= x^​(βˆ’1k)​(βˆ’1kβˆ’1)​(λ​k​x^k)2^π‘₯1π‘˜1π‘˜1superscriptπœ†π‘˜superscript^π‘₯π‘˜2\displaystyle\hat{x}\,\left(-\frac{1}{k}\right)\left(-\frac{1}{k}-1\right)\left(\lambda k\hat{x}\,^{k}\right)^{2}

and so on. All these terms add up to give

Ξ©^Ξ»,k​x^​Ω^Ξ»,kβˆ’1subscript^Ξ©πœ†π‘˜^π‘₯subscriptsuperscript^Ξ©1πœ†π‘˜\displaystyle\hat{\Omega}_{{\lambda},k}\,\hat{x}\,\hat{\Omega}^{-1}_{{\lambda},k}\, =\displaystyle= x^​{I+(βˆ’1k)​(λ​k​x^k)+12!​(βˆ’1k)​(βˆ’1kβˆ’1)​(λ​k​x^k)2+β‹―}^π‘₯𝐼1π‘˜πœ†π‘˜superscript^π‘₯π‘˜121π‘˜1π‘˜1superscriptπœ†π‘˜superscript^π‘₯π‘˜2β‹―\displaystyle\hat{x}\,\left\{I+\left(-\frac{1}{k}\right)\left(\lambda k\hat{x}\,^{k}\right)+\frac{1}{2!}\left(-\frac{1}{k}\right)\left(-\frac{1}{k}-1\right)\left(\lambda k\hat{x}\,^{k}\right)^{2}+\cdots\right\} (3.7)
=\displaystyle= x^(I+λ​k​x^k)1k^π‘₯superscriptπΌπœ†π‘˜superscript^π‘₯π‘˜1π‘˜\displaystyle\frac{\hat{x}\,}{\left(I+\lambda k\hat{x}\,^{k}\right)^{\frac{1}{k}}}

leading finally to the result

Ξ©^Ξ»,k​x^n​Ω^Ξ»,kβˆ’1={x^(1+λ​k​x^k)1k}nsubscript^Ξ©πœ†π‘˜superscript^π‘₯𝑛subscriptsuperscript^Ξ©1πœ†π‘˜superscript^π‘₯superscript1πœ†π‘˜superscript^π‘₯π‘˜1π‘˜π‘›\hat{\Omega}_{{\lambda},k}\,\hat{x}\,^{n}\hat{\Omega}^{-1}_{{\lambda},k}\,=\left\{\frac{\hat{x}\,}{\left(1+\lambda k\hat{x}\,^{k}\right)^{\frac{1}{k}}}\right\}^{n} (3.8)

which is precisely the same as (3.2). We, therefore, conclude that the class of operators (3.1) and (3.4) are essentially equivalent.

A cursory inspection of the operators Ξ©^Ξ»,ksubscript^Ξ©πœ†π‘˜\hat{\Omega}_{{\lambda},k}\, ((3.1) or (3.4)) helps in defining the relations

(Ξ©^Ξ»,k)βˆ’1=Ξ©^βˆ’Ξ»,ksuperscriptsubscript^Ξ©πœ†π‘˜1subscript^Ξ©πœ†π‘˜\left(\hat{\Omega}_{{\lambda},k}\,\right)^{-1}={\hat{\Omega}}_{-\lambda,k} (3.9)

and

Ξ©^Ξ»,k∘Ω^ΞΌ,k=Ξ©^Ξ»+ΞΌ,ksubscript^Ξ©πœ†π‘˜subscript^Ξ©πœ‡π‘˜subscript^Ξ©πœ†πœ‡π‘˜\hat{\Omega}_{{\lambda},k}\,\circ{\hat{\Omega}}_{\mu,k}={\hat{\Omega}}_{\lambda+\mu,k} (3.10)

These exhibit interesting consequences in that if Ξ©^Ξ»,k​x=ysubscript^Ξ©πœ†π‘˜π‘₯𝑦\hat{\Omega}_{{\lambda},k}\,x=y, then Ξ©^Ξ»,kβˆ’1​y=xsubscriptsuperscript^Ξ©1πœ†π‘˜π‘¦π‘₯\hat{\Omega}^{-1}_{{\lambda},k}\,y=x. Writing explicitly, if we have

y=Ξ©^Ξ»,k​x=x(1+λ​k​xk)1k𝑦subscript^Ξ©πœ†π‘˜π‘₯π‘₯superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜y=\hat{\Omega}_{{\lambda},k}\,x=\frac{x}{\left(1+\lambda kx^{k}\right)^{\frac{1}{k}}} (3.11)

then

x=Ξ©^Ξ»,kβˆ’1​y=y(1βˆ’Ξ»β€‹k​yk)1kπ‘₯subscriptsuperscript^Ξ©1πœ†π‘˜π‘¦π‘¦superscript1πœ†π‘˜superscriptπ‘¦π‘˜1π‘˜x=\hat{\Omega}^{-1}_{{\lambda},k}\,y=\frac{y}{\left(1-\lambda ky^{k}\right)^{\frac{1}{k}}} (3.12)

where we have made use of (3.3) for the case when n=1𝑛1n=1. This is an interesting off-shoot of the foregoing considerations, allowing construction of a class of other operators possessing this unique property.

In more general terms, let us consider the operator

Ξ©^Ξ»,ΞΌ=exp⁑(λ​f​(x)β€‹βˆ‚x)subscript^Ξ©πœ†πœ‡πœ†π‘“π‘₯subscriptπ‘₯\hat{\Omega}_{\lambda,\mu}\,=\exp\left(\lambda f(x){\partial}_{x}\right) (3.13)

such that Ξ©^Ξ»,μ​x=ysubscript^Ξ©πœ†πœ‡π‘₯𝑦\hat{\Omega}_{{\lambda},\mu}\,x=y. In view of the above structures, the functions f​(x)𝑓π‘₯f(x) and f​(y)𝑓𝑦f(y) are invertible and therefore admit the forms

f​(y)=f​(x)1+λ​f​(x),f​(x)=f​(y)1βˆ’Ξ»β€‹f​(y)formulae-sequence𝑓𝑦𝑓π‘₯1πœ†π‘“π‘₯𝑓π‘₯𝑓𝑦1πœ†π‘“π‘¦f(y)=\frac{f(x)}{1+\lambda f(x)}\,,\qquad\qquad f(x)=\frac{f(y)}{1-\lambda f(y)} (3.14)

For instance, if we compute the action of Ξ©^Ξ»,ΞΌsubscript^Ξ©πœ†πœ‡\hat{\Omega}_{\lambda,\mu}\, on f​(x)=exp⁑(βˆ’ΞΌβ€‹x)𝑓π‘₯πœ‡π‘₯f(x)=\exp(-\mu x), say, we find

Ξ©^Ξ»,μ​x=x+ΞΌβˆ’1​ln⁑[1+λ​μ​eβˆ’ΞΌβ€‹x]subscript^Ξ©πœ†πœ‡π‘₯π‘₯superscriptπœ‡11πœ†πœ‡superscriptπ‘’πœ‡π‘₯\hat{\Omega}_{\lambda,\mu}\,x=x+\mu^{-1}\ln\left[1+\lambda\mu e^{-\mu x}\right] (3.15)

which constitutes a two–parameter (Ξ»,ΞΌ)πœ†πœ‡(\lambda,\mu) deformation of the derivative operator. Note, however, that Ξ©^Ξ»,ΞΌβ†’Iβ†’subscript^Ξ©πœ†πœ‡πΌ\hat{\Omega}_{\lambda,\mu}\,\rightarrow I in the limiting case when Ξ»β†’0β†’πœ†0\lambda\rightarrow 0 which is in complete conformity with what we expect. In a similar way, we also evaluate the limit of Ξ©^Ξ»,μ​xsubscript^Ξ©πœ†πœ‡π‘₯\hat{\Omega}_{\lambda,\mu}\,x (3.15) when ΞΌβ†’0β†’πœ‡0\mu\rightarrow 0 with the result

limΞΌβ†’0​{x+ΞΌβˆ’1​(λ​μ​eβˆ’ΞΌβ€‹x)+O​(ΞΌ)}=x+Ξ»subscriptlimβ†’πœ‡0π‘₯superscriptπœ‡1πœ†πœ‡superscriptπ‘’πœ‡π‘₯π‘‚πœ‡π‘₯πœ†\mbox{lim}_{\mu\rightarrow 0}\left\{x+\mu^{-1}\left(\lambda\mu e^{-\mu x}\right)+O(\mu)\right\}=x+\lambda (3.16)

This is obviously a manifestation of the finite difference operator limΞΌβ†’0​Ω^Ξ»,ΞΌ=exp⁑(Ξ»β€‹βˆ‚x)subscriptlimβ†’πœ‡0subscript^Ξ©πœ†πœ‡πœ†subscriptπ‘₯\mbox{lim}_{\mu\rightarrow 0}\hat{\Omega}_{\lambda,\mu}\,=\exp(\lambda{\partial}_{x}), characterised by the parameter Ξ»πœ†\lambda. We remark in passing that the form (3.15) can be alternatively represented as

Ξ©^Ξ»,μ​x=ΞΌβˆ’1​ln⁑[eμ​x+λ​μ]subscript^Ξ©πœ†πœ‡π‘₯superscriptπœ‡1superscriptπ‘’πœ‡π‘₯πœ†πœ‡\hat{\Omega}_{\lambda,\mu}\,x=\mu^{-1}\ln\left[e^{\mu x}+\lambda\mu\right] (3.17)

3.1 The associated derivative

The operation of the deformed derivative associated with Ξ©^Ξ»,ksubscript^Ξ©πœ†π‘˜\hat{\Omega}_{{\lambda},k}\, on a function f​(x)𝑓π‘₯f(x) can be expressed as

DxΩλ,k​f​(x)=f​(Ξ©^Ξ»,k​x)βˆ’f​(x)(Ξ©^Ξ»,k​x)βˆ’xsubscriptsubscript𝐷π‘₯subscriptΞ©πœ†π‘˜π‘“π‘₯𝑓subscript^Ξ©πœ†π‘˜π‘₯𝑓π‘₯subscript^Ξ©πœ†π‘˜π‘₯π‘₯~{}_{{\Omega}_{\lambda,k}}D_{x}f(x)=\frac{f(\hat{\Omega}_{{\lambda},k}\,x)-f(x)}{(\hat{\Omega}_{{\lambda},k}\,x)-x} (3.18)

Now

(Ξ©^Ξ»,k​x)βˆ’xsubscript^Ξ©πœ†π‘˜π‘₯π‘₯\displaystyle(\hat{\Omega}_{{\lambda},k}\,x)-x =\displaystyle= x(1+λ​k​xk)1kβˆ’xπ‘₯superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜π‘₯\displaystyle\frac{x}{\left(1+\lambda kx^{k}\right)^{\frac{1}{k}}}-x (3.19)
=\displaystyle= x​{1βˆ’(1+λ​k​xk)1k(1+λ​k​xk)1k}π‘₯1superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜\displaystyle x\left\{\frac{1-(1+\lambda kx^{k})^{\frac{1}{k}}}{(1+\lambda kx^{k})^{\frac{1}{k}}}\right\}

so that

DxΩλ,k​f​(x)=(1+λ​k​xk)1kx​[1βˆ’(1+λ​k​xk)1k]​{f​(x(1+λ​k​xk)1k)βˆ’f​(x)}subscriptsubscript𝐷π‘₯subscriptΞ©πœ†π‘˜π‘“π‘₯superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜π‘₯delimited-[]1superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜π‘“π‘₯superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜π‘“π‘₯~{}_{{\Omega}_{\lambda,k}}D_{x}f(x)=\frac{(1+\lambda kx^{k})^{\frac{1}{k}}}{x\left[1-(1+\lambda kx^{k})^{\frac{1}{k}}\right]}\left\{f\left(\frac{x}{\left(1+\lambda kx^{k}\right)^{\frac{1}{k}}}\right)-f(x)\right\} (3.20)

If we choose f​(x)=xn𝑓π‘₯superscriptπ‘₯𝑛f(x)=x^{n}, then

DxΩλ,k​xn=[[n]]Ξ»,k​xnβˆ’1subscriptsubscript𝐷π‘₯subscriptΞ©πœ†π‘˜superscriptπ‘₯𝑛subscriptdelimited-[]delimited-[]π‘›πœ†π‘˜superscriptπ‘₯𝑛1~{}_{{\Omega}_{\lambda,k}}D_{x}x^{n}=[[n]]_{\lambda,k}\,x^{n-1} (3.21)

where

[[n]]Ξ»,k=[[n]]Ξ»,k​(x)subscriptdelimited-[]delimited-[]π‘›πœ†π‘˜subscriptdelimited-[]delimited-[]π‘›πœ†π‘˜π‘₯\displaystyle[[n]]_{\lambda,k}\,=\,[[n]]_{\lambda,k}(x) =\displaystyle= {1(1+λ​k​xk)1k}nβˆ’1{1(1+λ​k​xk)1k}βˆ’1superscript1superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜π‘›11superscript1πœ†π‘˜superscriptπ‘₯π‘˜1π‘˜1\displaystyle\frac{\left\{\frac{1}{\left(1+\lambda kx^{k}\right)^{\frac{1}{k}}}\right\}^{n}-1}{\left\{\frac{1}{\left(1+\lambda kx^{k}\right)^{\frac{1}{k}}}\right\}-1} (3.22)
=\displaystyle= βˆ‘n=0∞(1+λ​k​xk)βˆ’nksuperscriptsubscript𝑛0superscript1πœ†π‘˜superscriptπ‘₯π‘˜π‘›π‘˜\displaystyle\sum_{n=0}^{\infty}\left(1+\lambda kx^{k}\right)^{-\frac{n}{k}} (3.23)

Note that [[n]]Ξ»,ksubscriptdelimited-[]delimited-[]π‘›πœ†π‘˜[[n]]_{\lambda,k} is now a function of xπ‘₯x.

3.2 Deformed inverse eigenfunctions

We have already seen that the ΩΩ\Omega–exponential functions Eλ​(x)subscriptπΈπœ†π‘₯E_{\lambda}(x) are the eigenfunctions of DxΞ©subscriptsubscript𝐷π‘₯Ξ©~{}_{\Omega}D_{x}. This enables us to write down the eigenvalue equation

DxΩ​Eλ​(μ​x)=μ​Eλ​(μ​x)subscriptsubscript𝐷π‘₯Ξ©subscriptπΈπœ†πœ‡π‘₯πœ‡subscriptπΈπœ†πœ‡π‘₯~{}_{\Omega}D_{x}E_{\lambda}(\mu x)=\mu E_{\lambda}(\mu x) (3.24)

where ΞΌπœ‡\mu is regarded as an eigenvalue of DxΞ©subscriptsubscript𝐷π‘₯Ξ©~{}_{\Omega}D_{x} with the corresponding eigenfunction Eλ​(μ​x)subscriptπΈπœ†πœ‡π‘₯E_{\lambda}(\mu x). Explicitly, this can be written as

Ξ©^Ξ»,k​Eλ​(μ​x)={1+μ​(Ξ©^Ξ»,kβˆ’I)​x}​Eλ​(μ​x)subscript^Ξ©πœ†π‘˜subscriptπΈπœ†πœ‡π‘₯1πœ‡subscript^Ξ©πœ†π‘˜πΌπ‘₯subscriptπΈπœ†πœ‡π‘₯\hat{\Omega}_{{\lambda},k}\,E_{\lambda}(\mu x)=\left\{1+\mu(\hat{\Omega}_{{\lambda},k}\,-I)x\right\}E_{\lambda}(\mu x) (3.25)

which reduces to

Ξ©^Ξ»,k​Eλ​(x)={1+(Ξ©^Ξ»,kβˆ’1)​x}​Eλ​(x)subscript^Ξ©πœ†π‘˜subscriptπΈπœ†π‘₯1subscript^Ξ©πœ†π‘˜1π‘₯subscriptπΈπœ†π‘₯\hat{\Omega}_{{\lambda},k}\,E_{\lambda}(x)=\left\{1+(\hat{\Omega}_{{\lambda},k}\,-1)x\right\}E_{\lambda}(x) (3.26)

for ΞΌ=1πœ‡1\mu=1. Rewriting (3.25), we have

Eλ​(μ​x)subscriptπΈπœ†πœ‡π‘₯\displaystyle E_{\lambda}(\mu x) =\displaystyle= Ξ©^Ξ»,kβˆ’1​{1+μ​(Ξ©^Ξ»,kβˆ’1)​x}​Eλ​(μ​x)subscriptsuperscript^Ξ©1πœ†π‘˜1πœ‡subscript^Ξ©πœ†π‘˜1π‘₯subscriptπΈπœ†πœ‡π‘₯\displaystyle\hat{\Omega}^{-1}_{{\lambda},k}\,\left\{1+\mu(\hat{\Omega}_{{\lambda},k}\,-1)x\right\}E_{\lambda}(\mu x) (3.27)
=\displaystyle= {1+μ​(1βˆ’Ξ©^Ξ»,kβˆ’1)​x}​Eλ​(μ​Ω^Ξ»,kβˆ’1​x)1πœ‡1subscriptsuperscript^Ξ©1πœ†π‘˜π‘₯subscriptπΈπœ†πœ‡subscriptsuperscript^Ξ©1πœ†π‘˜π‘₯\displaystyle\left\{1+\mu(1-\hat{\Omega}^{-1}_{{\lambda},k}\,)x\right\}E_{\lambda}(\mu\hat{\Omega}^{-1}_{{\lambda},k}\,x) (3.28)
=\displaystyle= {1+μ​(1βˆ’Ξ©^βˆ’Ξ»,k)​x}​Eλ​(μ​Ω^βˆ’Ξ»,k​x)1πœ‡1subscript^Ξ©πœ†π‘˜π‘₯subscriptπΈπœ†πœ‡subscript^Ξ©πœ†π‘˜π‘₯\displaystyle\left\{1+\mu(1-\hat{\Omega}_{-\lambda,k})x\right\}E_{\lambda}(\mu\hat{\Omega}_{-\lambda,k}\,x) (3.29)

where use has been made of the relation Ξ©^Ξ»,kβˆ’1=Ξ©^βˆ’Ξ»,ksubscriptsuperscript^Ξ©1πœ†π‘˜subscript^Ξ©πœ†π‘˜\hat{\Omega}^{-1}_{{\lambda},k}\,=\hat{\Omega}_{-\lambda,k}. Letting Ξ»β†’βˆ’Ξ»β†’πœ†πœ†\lambda\rightarrow-\lambda and ΞΌ=βˆ’1πœ‡1\mu=-1 in (3.29), we obtain

Eβˆ’Ξ»β€‹(βˆ’x)subscriptπΈπœ†π‘₯\displaystyle E_{-\lambda}(-x) =\displaystyle= {1+(Ξ©^Ξ»,kβˆ’1)​x}​Eβˆ’Ξ»β€‹(βˆ’Ξ©^Ξ»,k​x)1subscript^Ξ©πœ†π‘˜1π‘₯subscriptπΈπœ†subscript^Ξ©πœ†π‘˜π‘₯\displaystyle\left\{1+(\hat{\Omega}_{\lambda,k}-1)x\right\}E_{-\lambda}(-\hat{\Omega}_{\lambda,k}\,x) (3.30)
=\displaystyle= {1+(Ξ©^Ξ»,kβˆ’1)​x}​Ω^Ξ»,k​Eβˆ’Ξ»β€‹(βˆ’x)1subscript^Ξ©πœ†π‘˜1π‘₯subscript^Ξ©πœ†π‘˜subscriptπΈπœ†π‘₯\displaystyle\left\{1+(\hat{\Omega}_{\lambda,k}-1)x\right\}\hat{\Omega}_{\lambda,k}\,E_{-\lambda}(-x) (3.31)

Equations (3.26) and (3.31) lead to

Ξ©^Ξ»,k​Eλ​(x)​Ω^Ξ»,k​Eβˆ’Ξ»β€‹(βˆ’x)=Eλ​(x)​Eβˆ’Ξ»β€‹(βˆ’x)subscript^Ξ©πœ†π‘˜subscriptπΈπœ†π‘₯subscript^Ξ©πœ†π‘˜subscriptπΈπœ†π‘₯subscriptπΈπœ†π‘₯subscriptπΈπœ†π‘₯\hat{\Omega}_{{\lambda},k}\,E_{\lambda}(x)\hat{\Omega}_{\lambda,k}\,E_{-\lambda}(-x)=E_{\lambda}(x)E_{-\lambda}(-x) (3.32)

i.e.

Ξ©^Ξ»,k​{Eλ​(x)​Eβˆ’Ξ»β€‹(βˆ’x)}=Eλ​(x)​Eβˆ’Ξ»β€‹(βˆ’x)subscript^Ξ©πœ†π‘˜subscriptπΈπœ†π‘₯subscriptπΈπœ†π‘₯subscriptπΈπœ†π‘₯subscriptπΈπœ†π‘₯\hat{\Omega}_{{\lambda},k}\,\left\{E_{\lambda}(x)E_{-\lambda}(-x)\right\}=E_{\lambda}(x)E_{-\lambda}(-x) (3.33)

or

(Ξ©^Ξ»,kβˆ’I)​{Eλ​(x)​Eβˆ’Ξ»β€‹(βˆ’x)}=0subscript^Ξ©πœ†π‘˜πΌsubscriptπΈπœ†π‘₯subscriptπΈπœ†π‘₯0(\hat{\Omega}_{{\lambda},k}\,-I)\left\{E_{\lambda}(x)E_{-\lambda}(-x)\right\}=0 (3.34)

Hence

DxΩλ,k​{Eλ​(x)​Eβˆ’Ξ»β€‹(βˆ’x)}=0subscriptsubscript𝐷π‘₯subscriptΞ©πœ†π‘˜subscriptπΈπœ†π‘₯subscriptπΈπœ†π‘₯0~{}_{{\Omega}_{\lambda,k}}D_{x}\left\{E_{\lambda}(x)E_{-\lambda}(-x)\right\}=0 (3.35)

which clearly shows that the product Eλ​(x)​Eβˆ’Ξ»β€‹(βˆ’x)subscriptπΈπœ†π‘₯subscriptπΈπœ†π‘₯E_{\lambda}(x)E_{-\lambda}(-x) under the action of the deformed derivative operator DxΩλ,ksubscriptsubscript𝐷π‘₯subscriptΞ©πœ†π‘˜~{}_{{\Omega}_{\lambda,k}}D_{x} differentiates to zero. Ordinarily, we would expect that only constant functions are endowed with this property. An important consequence of this observation is that any function F​(x)𝐹π‘₯F(x), not necessarily a constant, with the property F​(x)=F​(Ξ©^​x)𝐹π‘₯𝐹^Ξ©π‘₯F(x)=F(\hat{\Omega}\,x) will differentiate to zero under the action of the generalised derivative DxΩλ,ksubscriptsubscript𝐷π‘₯subscriptΞ©πœ†π‘˜~{}_{{\Omega}_{\lambda,k}}D_{x}.

We now consider the case where Ξ©^Ξ»,ksubscript^Ξ©πœ†π‘˜\hat{\Omega}_{{\lambda},k}\, is identified with the translation operator, i.e., Ξ©^Ξ»,k=H^=ehβ€‹βˆ‚xsubscript^Ξ©πœ†π‘˜^𝐻superscriptπ‘’β„Žsubscriptπ‘₯\hat{\Omega}_{{\lambda},k}\,=\hat{H}\,=e^{h{\partial}_{x}}. It is then easy to see from (3.26) that

H^​Eh​(x)^𝐻subscriptπΈβ„Žπ‘₯\displaystyle\hat{H}\,E_{h}(x) =\displaystyle= {1+(H^βˆ’1)​x}​Eh​(x)1^𝐻1π‘₯subscriptπΈβ„Žπ‘₯\displaystyle\left\{1+(\hat{H}\,-1)x\right\}E_{h}(x) (3.36)
=\displaystyle= (1+h)​Eh​(x)1β„ŽsubscriptπΈβ„Žπ‘₯\displaystyle(1+h)E_{h}(x)

Consequently, the eigenfunctions of the translation operator H^^𝐻\hat{H}\, are exactly the same as those of the deformed derivative operator associated with H^^𝐻\hat{H}\,. On the other hand, if Ξ©^Ξ»,ksubscript^Ξ©πœ†π‘˜\hat{\Omega}_{{\lambda},k}\, is taken to be the qπ‘žq–dilation operator, i.e., Ξ©^Ξ»,k=Q^=exp⁑(ln⁑(q)​xβ€‹βˆ‚x)subscript^Ξ©πœ†π‘˜^π‘„π‘žπ‘₯subscriptπ‘₯\hat{\Omega}_{{\lambda},k}\,=\hat{Q}\,=\exp(\ln(q)x{\partial}_{x}), then we obtain

Eqβˆ’1​(x)=Eqβˆ’1​(βˆ’x)superscriptsubscriptπΈπ‘ž1π‘₯subscript𝐸superscriptπ‘ž1π‘₯E_{q}^{-1}(x)=E_{q^{-1}}(-x) (3.37)

as expected.

4 The Conformal (MΓΆbius) Transformation

The mathematical framework developed thus far will now be cast in a proper perspective so as to make contact with situations that hold promise for possible applications. The translation operator H^^𝐻\hat{H}\, and the qπ‘žq–dilation operator Q^^𝑄\hat{Q}\,, which give rise to the finite difference derivative and the qπ‘žq–derivative, respectively, may be regarded as generators of a one-dimensional affine group. In view of our consideration of the deformed derivative operator, of which H^^𝐻\hat{H}\, and Q^^𝑄\hat{Q}\, are special cases, it would seem instructive to visualise a situation where the operator Ξ©^Ξ»,ksubscript^Ξ©πœ†π‘˜\hat{\Omega}_{{\lambda},k}\,, affecting the generalisation, can indeed be assigned the role of an additional generator, resulting in some larger algebraic structure. To this end, we take recourse to the special conformal (MΓΆbius) transformation and carry out an embedding in conjunction with the generators H^^𝐻\hat{H}\, and Q^^𝑄\hat{Q}\,.

The action of a matrix M=(abcd)π‘€π‘Žπ‘π‘π‘‘M=\left(\begin{smallmatrix}a&b\\ c&d\end{smallmatrix}\right) on a variable xπ‘₯x is defined as

Mβ–·x=a​x+bc​x+d,a​dβ‰ b​cformulae-sequence▷𝑀π‘₯π‘Žπ‘₯𝑏𝑐π‘₯π‘‘π‘Žπ‘‘π‘π‘M\triangleright x=\frac{ax+b}{cx+d},\qquad ad\neq bc (4.1)

The operator Ξ©^Ξ»,ksubscript^Ξ©πœ†π‘˜\hat{\Omega}_{{\lambda},k}\, (cf. (3.1)) for k=1π‘˜1k=1 takes the form

Ξ©^=Ξ©^Ξ»,k=1=exp⁑(βˆ’Ξ»β€‹x2β€‹βˆ‚x)^Ξ©subscript^Ξ©πœ†π‘˜1πœ†superscriptπ‘₯2subscriptπ‘₯\hat{\Omega}\,=\hat{\Omega}_{\lambda,k=1}=\exp(-\lambda x^{2}{\partial}_{x}) (4.2)

whose action on a variable xπ‘₯x (cf. (3.2)) is given by

Ξ©^​x=x1+λ​x^Ξ©π‘₯π‘₯1πœ†π‘₯\hat{\Omega}\,x=\frac{x}{1+\lambda x} (4.3)

Defining the ΩΩ\Omega, Q𝑄Q and H𝐻H matrices as

Ξ©=(10Ξ»1),Q=(q1200qβˆ’12),H=(1h01)formulae-sequenceΞ©10πœ†1formulae-sequence𝑄superscriptπ‘ž1200superscriptπ‘ž12𝐻1β„Ž01\Omega=\left(\begin{array}[]{cc}1&0\\ \lambda&1\end{array}\right)\,,\qquad Q=\left(\begin{array}[]{cc}q^{\frac{1}{2}}&0\\ 0&q^{-\frac{1}{2}}\end{array}\right)\,,\qquad H=\left(\begin{array}[]{cc}1&h\\ 0&1\end{array}\right) (4.4)

the corresponding actions on xπ‘₯x are represented as

Ξ©β–·x=xλ​x+1,Qβ–·x=q​x,Hβ–·x=x+hformulae-sequenceβ–·Ξ©π‘₯π‘₯πœ†π‘₯1formulae-sequence▷𝑄π‘₯π‘žπ‘₯▷𝐻π‘₯π‘₯β„Ž\Omega\triangleright x=\frac{x}{\lambda x+1}\,,\qquad Q\triangleright x=qx\,,\qquad H\triangleright x=x+h (4.5)

The general MΓΆbius operator M𝑀M is then obtained via the composition

M𝑀\displaystyle M =\displaystyle= Ω​Q​HΩ𝑄𝐻\displaystyle\Omega\,Q\,H (4.6)
i.e.(abcd)i.e.π‘Žπ‘π‘π‘‘\displaystyle\text{i.e.}\qquad\left(\begin{array}[]{cc}a&b\\ c&d\end{array}\right) =\displaystyle= (q12q12​hq12​λq12​λ​h+qβˆ’12)superscriptπ‘ž12superscriptπ‘ž12β„Žsuperscriptπ‘ž12πœ†superscriptπ‘ž12πœ†β„Žsuperscriptπ‘ž12\displaystyle\left(\begin{array}[]{cc}q^{\frac{1}{2}}&q^{\frac{1}{2}}h\\ q^{\frac{1}{2}}\lambda&q^{\frac{1}{2}}\lambda h+q^{-\frac{1}{2}}\end{array}\right) (4.11)

Equivalently, we express the MΓΆbius transformations on the variable xπ‘₯x in the form

M^​x^𝑀π‘₯\displaystyle\hat{M}\,x =\displaystyle= Ξ©^​Q^​H^​x^Ξ©^𝑄^𝐻π‘₯\displaystyle\hat{\Omega}\,\,\hat{Q}\,\,\hat{H}\,\,x (4.12)
=\displaystyle= exp⁑[βˆ’Ξ»β€‹x2β€‹βˆ‚x+ln⁑(q)​xβ€‹βˆ‚x+hβ€‹βˆ‚x]​xπœ†superscriptπ‘₯2subscriptπ‘₯π‘žπ‘₯subscriptπ‘₯β„Žsubscriptπ‘₯π‘₯\displaystyle\exp\left[-\lambda x^{2}{\partial}_{x}+\ln(q)x{\partial}_{x}+h{\partial}_{x}\right]\,x (4.13)

It turns out that a​dβˆ’b​c=1π‘Žπ‘‘π‘π‘1ad-bc=1. Thus the set of 2Γ—2222\times 2 matrices M𝑀M generate the S​L​(2)𝑆𝐿2SL(2) group structure. In other words, the operator Ξ©^^Ξ©\hat{\Omega}\, serves as an extra generator, in addition to the other two generators typified by the translation operator H^^𝐻\hat{H}\, and the qπ‘žq–dilation operator Q^^𝑄\hat{Q}\,, to generate the group S​L​(2)𝑆𝐿2SL(2) as well as its subgroups. The operator Ξ©^^Ξ©\hat{\Omega}\, is designated as the reduced MΓΆbius transformation operator and conforms to the realisation of the differential operators in view of the transformation (4.1).

5 Concluding Remarks

A modest attempt has been made to construct a generalised version of the deformed derivative operators within the context of a linear operator Ξ©^^Ξ©\hat{\Omega}\, whose action on functions of a real variable is considered to be multiplicative. The veracity of the mathematical formulation is checked against suitable illustrative examples. We note that the familiar forms of the finite difference and the qπ‘žq–derivatives are readily obtained as particular cases of the generalised structure. Such an observation lends credence to the validity of the procedure adopted in carrying out this construction. We have also addressed, though briefly, the possibility of casting the operator Ξ©^^Ξ©\hat{\Omega}\, in a format compatible with the special conformal or reduced MΓΆbius transformation operator. The inclusion of this operator, along with the translation operator H^^𝐻\hat{H}\, and the qπ‘žq–dilation operator Q^^𝑄\hat{Q}\,, to generate the S​L​(2)𝑆𝐿2SL(2) group is expected to be significant in seeking further applications to situations of physical interest such as the conformal transformations. The construction also forms a natural paradigm to investigate generalisation of the qπ‘žq–oscillators and the qπ‘žq–calculus.

Acknowledgements

The first author is grateful to Prof. E. Zeidler for the kind hospitality at the Max Planck Institute for Mathematics in the Sciences, Leipzig, where this work was carried out. The second author is supported by a research fellowship of the Royal Commission for the Exhibition of 1851.

References

  • [1] F. H. Jackson, On qπ‘žq–functions and a certain difference operator, Trans. Royal Soc. Edinburgh 46 (1908) 253-281; Basic Integration, Quart. J. Math. Oxford Series 2 (1951) 1-16.
  • [2] M. Arik and D. D. Coon, Hilbert spaces of analytic functions and generalised coherent states, J. Math. Phys. 17 (1976) 524-527.
  • [3] H. Exton, qπ‘žq–Hypergeometric Functions and Applications, E. Harwood, Chichester (1983).
  • [4] A. K. Agarwal, E. G. Kalnins and W. Miller, Canonical equations and symmetry techniques for qπ‘žq–series, SIAM J. Math. Anal. 18 (1987) 1519-1538.
  • [5] V. G. Drinfeld, Quantum groups, In Proc. International Congress of Mathematicians, Academic Press, New York (1987) pp 798-820.
  • [6] L. D. Faddeev, N. Y. Reshetikhin and L. A. Takhtajan, Quantisation of Lie groups and Lie algebras, Leningrad Math. J. 1 (1990) 193-225.
  • [7] M. Arik, The qπ‘žq–difference operator, the quantum hyperplane, Hilbert spaces of analytic functions and qπ‘žq–oscillators, Z. Phys. C 51 (1991) 627-632.
  • [8] L. C. Biedenharn and M. A. Lohe, Quantum Group Symmetry and qπ‘žq–Tensor Algebras, World Scientific, Singapore (1995).
  • [9] A. Klimyk and K. SchmΓΌdgen, Quantum Groups and Their Representations, Springer-Verlag (1997), and references therein.